Research Progress on the Synergy Mechanism of Dietary Fiber and Prebiotics - Zhao, Hongyu (International Journal of Agriculture and Food Sciences Research, 2025)
As a chronic disease seriously affecting human health, diabetes has seen a significant upward trend in global incidence. Data reported by the International Diabetes Federation (IDF) indicates that the quantity of diabetic individuals around the world has exceeded 500 million. Within China, the prevalence rate of diabetes has surpassed 12%, and nearly 35% of the adult population are in the pre-diabetic stage, indicating an extremely severe situation. Dietary fiber and prebiotics offer numerous benefits to human health, and their synergistic effects have garnered extensive attention in recent years. This article synthesizes relevant studies to elaborate on the definitions and classifications of dietary fiber and prebiotics, and details the impacts and mechanisms of their individual and synergistic actions on gut microbiota, intestinal barrier function, metabolic regulation, immune regulation, and other aspects. Dietary fiber can be processed by gut microbiota to boost the proliferation of friendly bacteria and regulate the intestinal barrier; prebiotics may specifically trigger the multiplication of good bacteria. Their synergistic effects demonstrate more significant outcomes than individual actions in regulating gut microecology, improving metabolic diseases, enhancing immunity, etc., providing a theoretical basis for promoting human health through dietary interventions.